FAST FOURIER TRANSFORM (FFT) UNTUK ANALISIS SINYAL SUARA DOPPLER ULTRASONIK - Arif Syaifuddin; Suryono Suryono (Youngster Physics Journal, 2014)
The vibration is a physical phenomenon that frequently occur in a system. This study examines the Doppler effect that occurs in a system by observing signals generated sound system with ultrasonic inspection methods and analyzes these signals to function Fast Fourier Transform (FFT) Matlab. The system is made by utilizing the collision object being towed magnetic field. Collision time is controlled by the microcontroller ATmega16 is used as a reference signal. The experiments were performed 3 times with a delay variation interval or different. The research data in the form of a frequency output signal microcontroller port and the reflected sound wave Doppler ultrasound fetal Doppler devices recording the results using computer software scope version 1.31. The signal was tested by using a fast Fourier transform to look at the frequency domain signal using Matlab 2013 on computer programming. The test results show the system has a lot of FFT frequency. But can be observed the 3 dominant frequency system. The test results compared to the reference frequency FFT shows the amount equal to the sum frequency generated by the microcontroller mean Doppler frequency spectrum of the sound is 387.597 Hz.Keywords: Signal, Doppler Effect, FFT, Ultrasonic Inspection, Dominant Frequency